2011
DOI: 10.1007/s11064-010-0373-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Dependent Inhibition of Gelatinases by Dietary Antioxidants in Rat Astrocytes and Sera of Multiple Sclerosis Patients

Abstract: We investigated whether polyphenols modulate the expression and activity of the enzymes gelatinases A (MMP-2) and B (MMP-9), involved in the pathogenesis of multiple sclerosis (MS). LPS-activated primary rat astrocytes were treated with the flavonoids quercetin (QRC) and cathechins [green tea extract (GTE)] and the non-flavonoids resveratrol (RSV) and tyrosol/hydroxytyrosol (Oliplus). As assessed by zymography and RT-PCR, RSV and Oliplus, but not QRC and GTE, dose-dependently inhibited the LPS-induced levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 51 publications
(48 reference statements)
2
31
0
Order By: Relevance
“…As polyphenols also have chelating properties (Hider, Liu, & Khodr, ; Le Nest et al, ), and can inhibit MMP activity (Demeule, Brossard, Page, Gingras, & Beliveau, ; Lin et al, ; Park, Kim, & Kim, ), the inhibition of the MMPs by the extracts may be ascribed to the chelating activity of the phenolic compounds present in M. comosum bulbs and therefore to their structure. Indeed, we have previously shown that polyphenols exert their inhibitory effects on MMPs displaying different mechanisms of action depending on their structure, being flavonoids more effective than nonflavonoids in inhibiting the in‐gel activity of MMP‐2 and MMP‐9 (Liuzzi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…As polyphenols also have chelating properties (Hider, Liu, & Khodr, ; Le Nest et al, ), and can inhibit MMP activity (Demeule, Brossard, Page, Gingras, & Beliveau, ; Lin et al, ; Park, Kim, & Kim, ), the inhibition of the MMPs by the extracts may be ascribed to the chelating activity of the phenolic compounds present in M. comosum bulbs and therefore to their structure. Indeed, we have previously shown that polyphenols exert their inhibitory effects on MMPs displaying different mechanisms of action depending on their structure, being flavonoids more effective than nonflavonoids in inhibiting the in‐gel activity of MMP‐2 and MMP‐9 (Liuzzi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that flavonoids and nonflavonoids inhibit MMP-9 levels with different mechanisms possibly related to their different structure: flavonoids, such as quercetin and the cathechins from green tea, inhibit MMP-9 directly; while non flavonoids, such as resveratrol and tyrosol/hydroxytyrosol from olive oil, inhibit its expression [113]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that genetics and environmental factors are involved in the pathology of MS. Accumulating evidence indicates that oxidative stress is an important factor involved in the pathogenesis of MS. Oxidative stress activates some mechanisms that lead to glia-mediated inflammation and neural damage [16].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are natural phytochemicals and they are secondary metabolites produced in plants to defend themselves from cellular stress. The interest in polyphenols is related to their well-known antioxidant activities which are reported to have positive effects on human health, due to their presence in dietary sources such as fruits, vegetables, wine, spices and herbs [16]. Green tea, prepared from the leaves of Camellia sinensis, is one of the popular beverages that are reported to have a number of beneficial health effects, including anti-inflammatory, anti-thrombotic and anticancer activities [12].…”
Section: Introductionmentioning
confidence: 99%